Effect of Simulated Eating Movement Training on Upper Limb Function in Hemiplegic Stroke Patients - Yannan CHEN; Xiaoqiong LIN; Wenxia ZHANG; Cui'e FENG; Jinxiu CHEN (康复学报)
Objective:To observe the effect of simulated eating movement training based on the principle of training and learning to stroke patients with hemiplegic upper limb on motor function and activities of daily living, so as to provide an economical, effective and easy rehabilitation nursing method for stroke patients with hemiplegia.Methods:Sixty subjects were recruited according to the inclusion and exclusion criteria. They were randomly divided into experimental group and control group, 30 cases each group. All subjects received routine treatment and rehabilitation nursing, while the experimental group received simulated eating movement training every day and successfully completed the action 50 times a day for 3 months. The changes of Fugl-Meyer assessment scale (FMA), Barthel Index (BI), clinical neurologic deficit scale (CNDS) about hemiplegic upper limb in the two groups were observed before test, 1 month after test and 3 months after test.Results:FMA score and BI about hemiplegic upper limb in the experimental group were significantly different compared with those in the control group (P<0.01) after 1 month and 3 month of test. There was no significant difference in the score of CNDS between the two groups (P>0.05).Conclusion:Simulated eating movement training can improve the motor function of stroke patients with hemiplegic upper limb and the self-care ability of stroke patients.